Features of the formation of the ontogenetic structure of the cenopopulation and seed productivity of Sanguisorba officinalis in the conditions of forest and forest‐steppe vegetation of the Middle Volga region, Russia - S. A. Dubrovnaya; L. Z. Khusnetdinova; O. A. Timofeeva (Юг России: экология, развитие)
The purpose of this work is to study the features of the life cycle of Sanguisorba officinalis in various types of vegetation in the Republic of Tatarstan, Russia. We used traditional methods for studying the cenopopulation, analysis of the calendar age of plants of various ontogenetic states, and potential and actual seed productivity. Under broad‐leaved forest conditions, a young normal population was formed on the basis of slowly developing plants. In conditions of open communities, young cenopopulations were formed on the basis of intensive seed reproduction processes. The young cenopopulation can be recommended for further study in biomass exploitation. The predominance of long‐lived vegetative and immature plants in the conditions of a broad‐leaved forest is associated with difficulties in the transition of individuals to sexual reproduction. The maintenance of numbers is carried out through vegetative growth and reproduction. With deterioration of ecological and coenotic conditions, above‐ground shoots were not formed but regressive‐quasisenile coenopopulations were formed. Seed productivity was determined by ecological and cenotic conditions. On the steppe meadow of the Bugulma district, the lowest seed productivity index was 9 %. The lowest indicator of the trait “Number of full‐fledged seeds” (the average indicator was 7), low seed germination and germination energy were also noted there. The highest values of these indicators were noted n glades of the broad‐leaved areas of the same region. The realization of the reproductive system of Sanguisorba officinalis even under extreme conditions and the survival of the species in various types of vegetation suggest that the territory of the Republic of Tatarstan is included in the ceno‐area of the species. This will permit the creation of plantations in the republic.